1991
DOI: 10.1111/j.2042-7158.1991.tb06685.x
|View full text |Cite
|
Sign up to set email alerts
|

Akinesia due to catecholamine depletion in mice is prevented by caffeine. Further evidence for an involvement of adenosinergic system in the control of motility

Abstract: The administration of reserpine with alpha-methyl-p-tyrosine (2.5 and 200 mg kg-1 i.p., 24 and 3 h before the test, respectively) induced a marked akinesia in mice. This effect was significantly and dose-dependently reversed by the methylxanthine, caffeine. The anti-akinetic effect of caffeine within a pattern of catecholamine depletion has been interpreted as a dopamine mimetic activity of this drug. The possible involvement of the adenosine system in this effect of caffeine is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…This has been repeatedly demonstrated in a number of experimental models involving rodents pretreated with D 2 receptor antagonists, reserpine, or MPTP or after genetic inactivation of D 2 receptors Popoli et al, 1991;Kanda et al, 1994;Giménez-Llort et al, 1995;Pollack and Fink, 1995;Malec, 1997;Shiozaki et al, 1999;Ward and Dorsa, 1999;Wardas et al, 1999;Aoyama et al, 2000;Chen et al, 2001;Ferré et al, 2001;Hauber et al, 2001) and involving MPTP-treated monkeys (Kanda et al, 1998a,b;Grondin et al, 1999). The results of these experiments suggest that A 2A receptor antagonists can be useful in the treatment of Parkinson's disease.…”
Section: Interactions Between Adenosinementioning
confidence: 60%
See 1 more Smart Citation
“…This has been repeatedly demonstrated in a number of experimental models involving rodents pretreated with D 2 receptor antagonists, reserpine, or MPTP or after genetic inactivation of D 2 receptors Popoli et al, 1991;Kanda et al, 1994;Giménez-Llort et al, 1995;Pollack and Fink, 1995;Malec, 1997;Shiozaki et al, 1999;Ward and Dorsa, 1999;Wardas et al, 1999;Aoyama et al, 2000;Chen et al, 2001;Ferré et al, 2001;Hauber et al, 2001) and involving MPTP-treated monkeys (Kanda et al, 1998a,b;Grondin et al, 1999). The results of these experiments suggest that A 2A receptor antagonists can be useful in the treatment of Parkinson's disease.…”
Section: Interactions Between Adenosinementioning
confidence: 60%
“…• The drug is developed for one coreceptor to modulate another coreceptor at the recognition level (binding pocket (Fuxe and Ungerstedt, 1974;Fredholm et al, 1983;Herrera-Marschitz et al, 1988;Casas et al, 1988;Popoli et al, 1991Jiang et al, 1993Kanda et al, 1994) and recent work (Malec, 1997;Kanda et al, 1998a,b;Grondin et al, 1999;Shiozaki et al, 1999;Ward and Dorsa, 1999;Wardas et al, 1999;Aoyama et al, 2000;Strömberg et al, 2000;Chen et al, 2001;Ferré et al, 2001;Fuxe et al, 2001;Hauber et al, 2001;Pinna et al, 2001;Morelli and Wardas, 2001; T. Chase, personal communication).…”
Section: Possible Targets For Drugs Acting On Heteromeric Receptormentioning
confidence: 99%
“…Three other studies reported less coffee consumption among PD cases than controls [18,25,26], although this was significant in only one [26]. Both ethanol [27,28] and caffeine [29][30][31] affect dopamine transmission and turnover in the basal ganglia and other brain regions.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, different biological and experimental evidence suggests a real role of coffee and caffeine consumption in reducing the risk of PD [40][41][42]. Animal models in particular indicate that caffeine may act not just by preventing PD but simply by delaying the onset of disease symptoms [42][43][44].…”
Section: Discussionmentioning
confidence: 99%